Transcriptional survey of the light-induced anthocyanin pathway in non-GM purple tomatoes - Silvia Gonzali; Jacopo Menconi; Pierdomenico Perata (Frontiers in Plant Physiology)
Anthocyanins are polyphenolic compounds with antioxidant capacity, free radical scavenging power, and signaling activities in animal pathogenesis-associated pathways, thus playing an important role as nutraceuticals. Tomato fruits do not usually contain anthocyanins because their biosynthesis is switched off in these organs, but anthocyanin-enriched purple tomatoes have been produced in recent years. The varieties obtained by breeding express a functional copy of the R2R3-MYB transcription factor AN2-like, necessary to start the biosynthetic pathway, and do not produce a functional MYB-ATV repressor. The combination of these traits allows the accumulation of anthocyanins in tomatoes, strengthened under specific environmental factors such as high light intensity or low temperatures. Light starts anthocyanin synthesis and gradually extends its distribution on the fruit exocarp. The analyses carried out in the present study indicate that anthocyanin biosynthesis triggered by light is under HY5 control. However, the process is not active in mesocarp for the absence of the bHLH factor AN1, necessary to produce the MBW complex inducing the late enzymes of the biosynthetic pathway, as a consequence of insufficient expression of the R2R3-MYB gene AN2-like. This occurs since light cannot be perceived in the tissues underneath the skin because of the solar shield produced by the anthocyanins accumulated in the exocarp and for the activation of regulatory loops controlling HY5 levels. This is shown by the expression of genes involved in the production of photoreceptors and in the light signaling chain operating upstream of the anthocyanin pathway and responsible for its activation.